A least cost transmission planning model considering operation cost - Alayo, Jorge Hans [UNESP] (De Gruyter, 2014)
Existing transmission planning models consider basic aspects of the problem. In practice, a transmissionutility needs to model other important details such as operation cost of the power system. In this article, a least cost transmission expansion model is proposed considering the operation cost in order to model the trade-off between building new transmission capacity and increasing the power system's operation cost. The proposed model is transformed into a mixed integer linear programming problem using linearization techniques and solved with CPLEX. Finally, results of the model for the Garver test system and IEEE 24-bus test system are shown. © 2014 by Walter de Gruyter Berlin/Boston.
Keywords: disjuctive linear model; multistage model; operation cost; transmission planning